2013
DOI: 10.1016/j.aos.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Performance measurement, modes of evaluation and the development of compromising accounts

Abstract: In this paper we develop the concept of compromising accounts as a distinctive approach to the analysis of whether and how accounting can facilitate compromise amongst organizational actors. We take the existence of conflicting logics and values as the starting point for our analysis, and directly examine the ways in which the design and operation of accounts can be implicated in compromises between different modes of evaluation and when and how such compromises can be productive or unproductive. In doing so, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
249
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(262 citation statements)
references
References 65 publications
(103 reference statements)
9
249
1
3
Order By: Relevance
“…This influence was most apparent in planning procedures and meetings, where stakeholders had the opportunity to openly discuss their respective performance aims and ask questions to the stakeholders of another logic. The role of PM as a means to reconcile logics is similar to what was found by Chenhall et al (2013): accounting practices can enhance compromise across stakeholder groups with divergent views if they are designed to be both about 'learning and uniqueness' (e.g., by encompassing narratives, case studies, qualitative data) and about 'consistency and competition' (e.g., standardized metrics, financial KPIs, quantitative data).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This influence was most apparent in planning procedures and meetings, where stakeholders had the opportunity to openly discuss their respective performance aims and ask questions to the stakeholders of another logic. The role of PM as a means to reconcile logics is similar to what was found by Chenhall et al (2013): accounting practices can enhance compromise across stakeholder groups with divergent views if they are designed to be both about 'learning and uniqueness' (e.g., by encompassing narratives, case studies, qualitative data) and about 'consistency and competition' (e.g., standardized metrics, financial KPIs, quantitative data).…”
Section: Discussionmentioning
confidence: 75%
“…Over the past years, research in PM has progressively shifted from the design of effective tools (e.g., frameworks and systems) to the exploration of how PM practices can enable positive behaviors, such as creative discussions (Chenhall et al, 2013), high levels of workforce participation (Groen et al, 2012) and individual improvements (Micheli and Mari, 2014). For example, Koufteros et al (2014) showed that the link between PM systems and performance depends not simply on how systems are structured, but how stakeholders use them.…”
Section: Performance Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, instead of studying how compromises between incompatible logics can be designed into performance measurement systems (PMS) (cf. Chenhall et al, 2013;Sundin et al, 2010), Carlsson-Wall et al (forthcoming) examine how managers used the information from a PMS to compromise between sports and business logics within a Swedish football organisation. They find that the compatibility of the two logics varied between situations, and that situation-specific compromises were made based on PMS.…”
Section: Institutional Logics Institutional Complexity and Hybrid Omentioning
confidence: 99%
“…Chenhall et al, 2013), that is, that appropriate mechanisms are in place to reinforce all competing identities to organizational members. In this way, a nonprofit could potentially adopt new identities with less opportunity for them to be seen to threaten existing identities.…”
Section: Aggregationmentioning
confidence: 99%